2019
DOI: 10.1002/jsfa.10126
|View full text |Cite
|
Sign up to set email alerts
|

The effect of an additive containing three Lactobacillus species on the fermentation pattern and microbiological status of silage

Abstract: BACKGROUND: Appropriate combinations of lactic acid bacteria (LAB) strains should be selected to optimize the ensiling process, and the additives should be adjusted to the ensiled forage crops. The aim of this study was to determine the effect of inoculation with three Lactobacillus species on the chemical parameters and microbiological quality (beneficial and harmful microbiota) of grass silage. RESULTS: Three species: L. paracasei (LPa), L. brevis (LB) and L. plantarum (LPl), isolated from sugar beet silage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 56 publications
0
17
0
Order By: Relevance
“…It can ferment feedstuffs to volatile fatty acids, microbial proteins, and vitamins, which play important roles in animal health and production [ 4 , 5 ]. Sometimes, it has to deal with lower quality fodder or silage [ 6 ]. Among the microbiota, bacteria are the most abundant, diverse, and metabolically active species in the rumen [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…It can ferment feedstuffs to volatile fatty acids, microbial proteins, and vitamins, which play important roles in animal health and production [ 4 , 5 ]. Sometimes, it has to deal with lower quality fodder or silage [ 6 ]. Among the microbiota, bacteria are the most abundant, diverse, and metabolically active species in the rumen [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…The Sucrosorgo 506 bagasse silages were dominated by lactic acid, and in our study lactic acid concentrations were found to be higher than the minimum value (30 g/kg of DM) for proper lactic fermentation. The statistically significant (P = 0.000) higher content of acetic acid in silage inoculated with L. buchneri is indicative of heterofermentation (Fijałkowska et al, 2020).…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, lactic acid bacteria (LAB) accelerate lactic acid fermentation and reduce nutrition losses during the ensilage process (Wang et al, 2019). As reported by Fijałkowska et al (2020), the addition of LAB and combination of similar strains, to silage 'completely or almost completely inhibited the growth of toxin-producing fungi of the genera Aspergillus and Fusarium'. In order to increase the stability of silages against contamination by yeasts and molds, in 1996 scientists proposed the use of L. buchneri as a silage additive.…”
Section: Introductionmentioning
confidence: 95%
“…It affects nutrients composition, dry matter, palatability reduction and reduction in consumption of silage. The main fungi isolated from contaminated silages were Aspergillus, Perncillum and Fusarium genera followed by mucor, and others [6][7][8]. Homofermentative Lactobacilli includes Lactobacilli casei and L. plantarum that directly enhance the silage/haylage quality by preventing undesirable microbial growth via lowering surrounding pH.…”
Section: Introductionmentioning
confidence: 99%